Incidence and presence of virulence factors of Streptococcus suis infection in slaughtered pigs from Chiang Mai, Thailand - Padungtod P. (2014)
This study was designed to determine the incidence of Streptococcus suis infection in slaughtered pigs raised in industrial facility and backyard system in Chiang Mai City, Thailand. A total of 90 tonsils and submaxillary salivary gland/ lymph node samples from slaughtered pigs raised in industrial facility and 122 samples from slaughtered pigs raised in backyard system were collected. Isolation and identification of S. suis were conducted using standard bacteriological methods. Farm management and risk factor data were collected by a questionnaire. Serotyping and presence of virulence factor genes, epf, mrp and sly, were determined by multiplex PCR assay. The overall incidence of S. suis in this study was 9% (n = 212) and the incidence is significantly higher in districts located at a greater distance south of Chiang Mai City. S. suis serotype 2 was present more in healthy pigs (43%) than ill pigs (10%). Every S. suis isolate carried mrp and sly and ill pigs carried epf (80%) more than healthy pigs (57%). However, the probability of S. suis serotype 2 with epf + (0.245) detected in healthy pigs was higher than in ill pigs (0.08) indicating people may have a higher risk of being infected with S. suis from healthy than ill pigs.